2010
DOI: 10.1063/1.3428576
|View full text |Cite
|
Sign up to set email alerts
|

Drawn metamaterials with plasmonic response at terahertz frequencies

Abstract: The influences of substrate and metal properties on the magnetic response of metamaterials at terahertz region J. Appl. Phys.Electromagnetic metamaterials attract much attention since they can be engineered to exhibit optical properties not found in nature. Their fabrication, however, is challenging, especially in volume. We introduce drawing as a means of fabricating metamaterials, thus demonstrating a terahertz metamaterial. We codraw polymethyl-methacrylate and indium, producing several meters of metamateri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
66
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 15 publications
2
66
0
Order By: Relevance
“…After Ref. 8 . (iii) Simulated transmittance for an array of the metamaterial fiber shown in Figure 3, using the same methods and optical parameters presented in Ref.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After Ref. 8 . (iii) Simulated transmittance for an array of the metamaterial fiber shown in Figure 3, using the same methods and optical parameters presented in Ref.…”
Section: Representative Resultsmentioning
confidence: 99%
“…(iii) Simulated transmittance for an array of the metamaterial fiber shown in Figure 3, using the same methods and optical parameters presented in Ref. 8 . Note that in this case the fiber would exhibit a plasma frequency around 0.6 THz.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 At THz frequencies Tuniz et al, 13 experimentally demonstrated both magnifying and non-magnifying hyperlenses by fabricating a WM with the fiber drawing method. 14 The magnifying hyperlens was produced using a tapered section of the fiber that supports propagation of near-field features below the diffraction a) Electronic mail: samiul.habib@sydney.edu.au limit. However, fabrication of such larger tapers is also challenging.…”
mentioning
confidence: 99%
“…In the simulations the refractive index of Zeonex is taken to be 1.52. 14 The WM is oriented along the z-axis, and the objects to be imaged are placed in the xy-plane with the features to be resolved aligned on the x axis, see Fig. 1.…”
mentioning
confidence: 99%